Identification of Sannyasis in Paintings of Lepakshi Temple - Hawaldar, Asmita (Integrated Journal for Research in Arts and Humanities, 2023)
Lepakshi is a small town1 situated in Hindupur taluka of Anantpur district, Andhra Pradesh. It is famous for Veerbhadra temple built during Vijaynagar empire era having monumental temple architecture. The walls and ceilings of the temple were extensively decorated with Vijaynagar style. Now some of the paintings are detoriated. One of the mural paintings in Mahamandapa depicts Dakshinamoorti Shiv, one of the forms of Shiv. There are two sadhus in the same mural whose sects are unidentified yet. In this paper I have tried to prove that these sadhus are Dandi sannyasis of Dashnami shaiva sampradaya.